Changes in microbial composition and the prevalence of foodborne pathogens in crab marinated in soy sauce produced by six manufacturing plants. (25th August 2016) - Kim, Sun Ae; Choi, Eun Sook; Kim, Nam Hee; Kim, Hye Won; Lee, Na Young; Cho, Tae Jin; Jo, Jun Il; Kim, Soon Han; Lee, Soon Ho; Ha, Sang Do; Rhee, Min Suk
Abstract: BACKGROUND: The present study examined the changes in microbiological composition during the production process of crab marinated in soy sauce, potential microbial hazards, potential contamination routes and effective critical control points. Crab and soy sauce samples were obtained from six different manufacturing plants at different stages, and their microbiological content was comprehensively assessed by quantitative and qualitative analyses. RESULTS: The results revealed the following: (1) the final products contained 4.0 log colony‐forming units (CFU) g −1 aerobic plate counts (APCs) and 1.1 log CFU g −1 coliforms, which may have been introduced from the raw materials (the level of APCs in raw crab and soy sauce mixed with other ingredients was 3.8 log CFU g −1 and 4.0 log CFU mL −1 respectively); (2) marination of crab in soy sauce may allow cross‐contamination by coliforms; (3) only Bacillus cereus and Staphylococcus aureus were qualitatively detected in samples at different stages of manufacture (detection rate of 28 and 5.6% respectively), and these bacteria may impact the microbiological quality and safety of crab marinated in soy sauce; and (4) bacterial counts were either maintained or increased during the manufacturing process (suggesting that no particular step can be targeted to reduce bacterial counts). CONCLUSION: Proper management of raw materials and the marination process are effective critical control points, and alternative interventions may be needed to control bacterial quantity. The results provide important basic information about the production of crab marinated in soy sauce and may facilitate effective implementation of sanitary management practices in related industries and research fields. © 2016 Society of Chemical Industry